PENGARUH FRAUD HEXAGON TERHADAP KECURANGAN LAPORAN KEUANGAN PADA BUMN GO PUBLIC INDONESIA - Suryakusuma, Andy; Stephanus, Daniel Sugama (Ma Chung Press, 2023)
Financial statement fraud is a problem that often occurs in Indonesia and causes many losses. Therefore, the purpose of this study is to detect the emergence of potential fraud against financial statements using hexagon fraud analysis. Hexagon fraud analysis there are six dominant factors that can trigger the emergence of fraud against financial statements, namely pressure, opportunity, rationalization, capability, arrogance, and collusion. Pressure is projected with financial targets and personal financial needs, opportunities are projected with the nature of industry and audit quality, rationalization is projected with auditor opinions, the ability to be projected with CEO tenure, arrogance is projected with CEO duality and collusion is projected with political connection. The dependent variables in this study were measured using the F-Score Model to find out how much potential for fraud on financial statements. In this study, the population sample was determined by the criteria of state-owned companies listed on the Indonesia Stock Exchange, for the last 5 years, namely, 2017–2021 which have always reported their financial statements in rupiah. Quantitative methods are supported by panel data regression analysis techniques as well as hypothesis tests using the T test, as well as the determination coefficient test being the method used in this study. The results of this study show that financial targets, personal financial needs, nature of industry, audit quality, opinion auditors, CEO tenure, CEO duality and political connection have no influence on the potential emergence of fraud against financial statements.